Efektivitas Artificial Intelligence Text to Speech dalam Meningkatkan Keterampilan Membaca - Sarif, Suharia; AR, Amran (Universitas Islam Ahmad Dahlan Sinjai, 2024)
As a second international language, Arabic has an existence to be learned by the general public, especially in formal and non-formal educational institutions. The use of Artificial Intelligence (AI) technology in various aspects of life has brought significant impacts, including in the field of education and learning. One increasingly popular application of AI is Text-to-Speech (TTS), which allows computers to convert written text into audible voice. This study aims to help users understand Arabic text reading, especially for users who cannot read Arabic script. And can be one of the tools or alternatives in the process of learning Arabic to improve reading skills. AI text-to-speech (TTS) can be very useful in improving reading skills. One way that AI TTS can help is in Clear Pronunciation: AI TTS can produce clear and accurate sounds, helping listeners understand words correctly and mimic proper pronunciation.